STUDI PENGARUH INTENSITAS ULTRAVIOLET PADA FOTOKATALIS TiO2 SEBAGAI REDUKSI NO2 DAN MIKROORGANISME DALAM SISTEM VENTILASI RUANG - Suwasono, Tabah; Assomadi, Abdu Fadli (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2023)
NO2 concentrations in vehicles or near highways are much higher than those measured on monitors in the current network. Some measurements in highway and terminal areas are reported to exceed the established quality standards although some areas of NO2 concentrations are below the quality standards but from surveys and data analysis show a risk quotient value of more than 1 indicating that it is not safe to be in the area for the next 30 years. One method to reduce NO2 concentration is titanium dioxide (TiO2) illuminated by UV, the presence of UV can be studied related to the reduction of microorganisms. The research was conducted with the study of ultraviolet intensity on TiO2 photocatalyst in reducing NO2 and UV intensity on microorganisms. The data taken is secondary data. This was followed by finding design criteria, followed by material selection. Dimensional calculations are carried out based on the material and criteria determined, then the estimated reduction efficiency on NO2 and microorganisms can be carried out and adjusted to the quality standards of PerMenKes No. 1077 of 2011. The estimation results show that the room ventilation design using an intensity of 75.8 mW/cm2 on TiO2 photocatalyst is able to reduce NO2 by at least 52.53% with an inlet concentration of 0.067 ppm. The use of an intensity of 75.8 mW/cm2 in the space ventilation design was able to reduce microorganisms with a UV D90 dose value below 238.77 J/m2. The space ventilation design is estimated to be sufficient to supply home room air under non-smoking conditions with NO2 reduction results according to the standard and close to microorganisms.